1995
DOI: 10.2307/3870019
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis TCH4, Regulated by Hormones and the Environment, Encodes a Xyloglucan Endotransglycosylase

Abstract: Adaptation of plants to environmental conditions requires that sensing of external stimuli be linked to mechanisms of morphogenesis. The Arabidopsis TCH (for touch) genes are rapidly upregulated in expression in response to environmental stimuli, but a connection between this molecular response and developmental alterations has not been established. We identified TCH4 as a xyloglucan endotransglycosylase by sequence similarity and enzyme activity. Xyloglucan endotransglycosylases most likely modify cell walls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(136 citation statements)
references
References 48 publications
9
126
1
Order By: Relevance
“…It was therefore of interest to investigate whether xyloglucan chains undergo transglycosylation in the walls of living plant cells. Xyloglucan endotransglycosylases (XETs) are widespread in land plants [13][14][15][16][17][18][19], and numerous correlations between XET activity and wall loosening have been noted [5,7,[20][21][22][23][24]. XET cuts a xyloglucan chain (donor substrate)…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore of interest to investigate whether xyloglucan chains undergo transglycosylation in the walls of living plant cells. Xyloglucan endotransglycosylases (XETs) are widespread in land plants [13][14][15][16][17][18][19], and numerous correlations between XET activity and wall loosening have been noted [5,7,[20][21][22][23][24]. XET cuts a xyloglucan chain (donor substrate)…”
Section: Introductionmentioning
confidence: 99%
“…Kauschmann et al (1996) originally found that cbb1 (dwf1-6) could be rescued by exogenous application of brassinosteroids, suggesting that cbb1 (dwf1-6) is defective in brassinosteroid biosynthesis. They also analyzed the expression of genes known to be involved in cell elongation, such as ␥-tonoplast intrinsic protein (␥-TIP) (Hö fte et al, 1992;Phillips and Huttly, 1994), and cell wall-modifying enzymes such as xyloglucan endotransglycosylases, including TOUCH4 (TCH4) (Xu et al, 1995) and MERI5 (Medford et al, 1991). The steady-state mRNA levels of TCH4 and MERI5 were lowered, whereas the expression of ␥-TIP was increased in the cbb mutants.…”
mentioning
confidence: 99%
“…If whole plants had been used the treatments could potentially have generated secondary signals in the leaves that might have influenced root gene expression. No significant induction or reduction in GUS activity could be measured following 24 h exposure to the auxin IAA or the cytokinin BAP at physiologically relevant concentrations (50 μM each, Xu et al 1995) whilst gibberellic acid at the same concentration caused a 33% increase in promoter activity (P = 0.04; Fig. 5).…”
Section: Activity Of the Slreo Promoter In Mature Plantsmentioning
confidence: 99%